Microfinance Revisited: A Study with Reference to a Few Villages of Gorakhpur District, Uttar Pradesh - Srivastava, Atul (Indian Journal of Finance, 2012)
Microfinance is an initiative to provide credit to weaker sections of the society at an affordable cost. This paper emphasizes the areas which need special attention of the financial services providers. This paper analyzes the report of the Rangarajan Committee and explores the efficacy of the financial inclusion campaign. The paper also focuses on the challenges faced by bankers regarding microfinance. There are thousands of rural people who don’t even understand the meaning of financial products and services, let alone decide which are the best products/services suited to their needs as awareness regarding financial services/products/microfinance is abysmal among the rural poor. The present study makes an attempt to look into the different facets of microfinance, and the paper also tries to analyze and interpret the problems faced by bankers when they open a branch in the rural areas and also sheds light on the problems faced by the rural customers in getting credit from the banks.